(untitled) (International Journal of Mathematics and Physics, 2012)
In this paper presented the results of experimental study of pulsed plasma accelerator with coaxial geometry of electrodes, working in continuously filling mode at different initial pressure of working gas. The discharge current and plasma flow speed values is determined at gas density in range 0.05-5 Torr. It was shown anomalous plasma resistance at the initial moment of discharge, then the voltage in the first quarter of the discharge period was greater than the initial value . The magnetic field distribution between electrodes was obtained by magnetic probes and Rogowski belt (for outside of electrodes). It is shown, that the distribution of magnet field along axial direction of accelerator at low and medium vacuum has a significant influence on the process of plasma propagation, and at low density achievement maximal parameters of plasma flow, too.